Modelling the HAP swing impact on HAPS communication performance of wireless link. (24th March 2015) - Mingxiang, Guan; Le, Wang
The swing state of high–altitude platform (HAP) may critically impact the communication links of HAP stations (HAPS). Current studies have significant limitations and, therefore, do not accurately reflect the actual situation. This paper considers the impact platform swing has on wireless links through modelling. A wireless link model reflecting the swing state of HAP is proposed, and the problems associated with HAPs' instability are resolved. Furthermore, in this study issues concerning inefficient and poor communication quality, caused by significant random validation in receiving and transmitting signal in case of platform swing, are also solved. Finally, the validity of the proposed model is confirmed through numerical analysis and simulation.